Bone Cements: Review of Their Physiochemical and Biochemical Properties in Percutaneous Vertebroplasty - Provenzano, Matthew J. (AJNR Am J Neuroradiol, 2004)
Percutaneous vertebroplasty is an effective treatment for aggressive vertebral hemangiomas, osteoporotic vertebral compression fractures, spinal metastases, and myelomas. As percutaneous vertebroplasty is more commonly performed to treat various forms of back pain, new or modified cements are being used. This review examines the physiochemical and biomechanical properties of various bone cements and additives.